Graphene related magnetic materials: micromechanical exfoliation of 2D layered magnets based on bimetallic anilate complexes with inserted [FeIII(acac2-trien)]+ and [FeIII(sal2-trien)]+ molecules1. Issue 8 (14th August 2015) - Abhervé, Alexandre; Mañas-Valero, Samuel; Clemente-León, Miguel; Coronado, Eugenio
<x xml:space="preserve">Abstract</x> The Scotch tape method has been used for the exfoliation of layered coordination compounds formed by a 2D bimetallic anilate-based anionic network and Fe(iii) cationic complexes placed between or within the layers.